Intestinal Bacteroides Levels are Reduced by a Fruit and Vegetable Juice Concentrate. (29th May 2020) - van der Merwe, Marie; Moore, Damien; Hill, Jessica; Keating, Faith; Bloomer, Richard; Buddington, Randall; Bowman, Dale; Wang, Anyou
Abstract: Objectives: Phytochemicals from fruits and vegetables have the potential to reduce inflammation and improve overall health. This study evaluated the effect of an encapsulated fruit and vegetable juice concentrate (FVC) on the composition and abundances of intestinal microbiota in an overweight/obese, female population and the association with indicators of metabolic health and inflammatory status. Methods: The study was performed as a randomized, double blind, placebo-controlled trial with 57 asymptomatic, pre-menopausal, overweight/obese (BMI between 25 and 40 kg/m 2 ) females between 25–50 years of age and working in the healthcare field. Blood and fecal samples were collected before and after eight and sixteen weeks of daily supplementation with FVC. Metabolic and immune parameters were measured, and the gut microbiome was analyzed by sequencing of the V4 region of the 16SrRNA gene. Results: The FVC supplementation did not change serum cholesterol, HDL, LDL, triglycerides and fasting glucose, or fasting cytokine levels for MCP1, MIP-1β, TNF-α, IL-10, IL-1β, IL-6, and Leptin. Sequencing analysis revealed the most abundant phyla detected at baseline in this population were Firmicutes (75.75 ± 10.59%), Bacteroidetes (15.23 ± 12.5%), with Actinobacteria, Proteobacteria and Verrucomicrobia also present. The following genera was most abundant in the study population: Blautia (22 ± 12.86%), Roseburia (8.03 ± 7.34%), Coprococus (5.44 ± 4.0%), Faecalibatcerium ( 11.12 ± 8.12%) and Bacteroides ( 10.89 ± 9.56%). FCV supplementation did not result in significant taxonomic changes at the level of phyla, or alter alpha (Shannon Index) or beta diversity (Bray Curtis analysis). However, there was a consistent reduction in overall bacterial abundance in the FVC supplemented group. This reduction was primarily attributed to the decrease in the gram-negative, anaerobic genus, Bacteroides ( P  = 0.08). Conclusions: An encapsulated fruit and vegetable juice concentrate did not alter metabolic or inflammatory indicators in a healthy, overweight/obese female population, but resulted in a reduced abundance of the intestinal bacterial population, Bacteroides . Funding Sources: NSA LLC/The Juice Plus +® Company.